2021
DOI: 10.1136/bmjopen-2020-047508
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study: patients’ enduring concerns about discussing internet use in general practice consultations

Abstract: ObjectivesTo examine patients’ accounts of their use of the internet before seeing a general practitioner (GP) using thematic analysis of semistructured interviews.DesignQualitative semistructured interview study with transcripts analysed thematically.SettingPrimary care patients consulting with 10 GPs working at 7 GP practices of varying sizes and at a range of locations around London and the Southeast of England.Participants28 adult patients: 16 women and 12 men ranging in age from 18 to 75 from a range of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other reviews have concluded that the retrieval of information from web-based resources such as social media can enhance collaboration and relationships between people with chronic conditions and HCPs if the information is discussed in clinical encounters [ 13 , 14 ]. However, judging from other reviews and studies, people with chronic conditions may be reluctant to present their information because of the potentially negative reactions from HCPs [ 12 , 13 , 15 , 88 , 89 ]. Therefore, HCPs may not realize that people with chronic conditions are equipped with information from peers on social media unless they actively address this subject in clinical consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews have concluded that the retrieval of information from web-based resources such as social media can enhance collaboration and relationships between people with chronic conditions and HCPs if the information is discussed in clinical encounters [ 13 , 14 ]. However, judging from other reviews and studies, people with chronic conditions may be reluctant to present their information because of the potentially negative reactions from HCPs [ 12 , 13 , 15 , 88 , 89 ]. Therefore, HCPs may not realize that people with chronic conditions are equipped with information from peers on social media unless they actively address this subject in clinical consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will involve examining the experiences and perspectives of older adults with LTCs regarding their online community use and interactions with HCPs. The popularity of online communities reflects broader trends of using the Internet for health-related information as governments and health authorities have encouraged people to become more independent and proactive regarding their own healthcare and health management (Cuteanu et al, 2021). However, despite an increasing democratization of access to health information and growth of Internet use among older adults, research has shown that problems can arise if there is a misalignment between information provided online and by HCPs or fear of a challenge to HCP’s authority (Litchman et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…This involved selecting and analyzing posts from one publicly accessible UK-based website and discussion forum explicitly targeting older adults. A description of the characteristics of the online discussion forum and website features and user features is provided in the study protocol (Lawless et al, 2020). To identify the website, we searched Google using the advanced search function for older adults’ online communities using combinations of keywords and Boolean operators.…”
Section: Methodsmentioning
confidence: 99%